Technology Transfer Between the US, China and Taiwan : Moving Knowledge. - Fuller, Douglas B. (Routledge Research on Taiwan Series., 2013)
Examining the flow of technical knowledge between the US, Taiwan and Mainland China over the last sixty-five years, this book shows that the technical knowledge that has moved between these states is vast and varied. It includes the invention and production of industrial goods, as well as knowledge of the patterns of corporate organization and management. Indeed, this diversity is reflected in the process itself, which is driven both by returning expatriates with knowledge acquired overseas and by successful government intervention in acquiring technology from multinational firms. <E.